(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The objective of this research was to conduct a systematic literature review (SLR) from which Digital Storytelling Media Online via Gamification Model To promote of Digital Literacy Skills for undergraduate students in Thailand was conceptualized. A total of 72 topics from local and international books, research papers, articles, and relevant documents were analyzed and synthesized using the systematic literature review method. Initially using a mixed methods approach, a six-step Digital Literacy Process (DSML-Gami Model) was conceptualized. After that, a panel of nine experts gave input into the model’s design . The six DSML-Gami Model steps included; They consist of 1) information accessibility, 2) management, 3) evaluation, 4) conclusion, 5) creation, and 6) communication. The results of the model encourage undergraduate students to use digital literacy skill. Also, students who studied with DSML-Gami Model ability were satisfied with the model